Corticosteroid Responsiveness in Acute Respiratory Distress Syndrome of Different Aetiologies: A Two-Patient Case Series - Rahmad Dwi Saputra; Arie Zainul Fatoni; Rudy Vitraludyono (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Acute respiratory distress syndrome (ARDS) is a life-threatening, biologically heterogeneous form of acute hypoxaemic respiratory failure arising from a broad spectrum of direct and indirect pulmonary insults. Although lung-protective ventilation and supportive care remain the foundation of management, the role of corticosteroids is still debated, with benefit concentrated in carefully selected patients and specific inflammatory phenotypes. We describe two patients whose ARDS arose from distinct aetiologies yet responded favourably to low-dose corticosteroid therapy. Case Presentation: The first patient was a 14-year-old girl with Marfan syndrome who developed abrupt severe hypoxaemia with bilateral infiltrates within six hours of massive intraoperative transfusion during scoliosis correction, consistent with post-transfusion (transfusion-related) acute lung injury. The second was a 39-year-old man with severe ARDS from bilateral pulmonary contusion after blunt chest trauma, complicated by Acinetobacter baumannii and Enterobacteriaceae hospital-acquired pneumonia. Both received lung-protective mechanical ventilation with individualised positive end-expiratory pressure and intravenous methylprednisolone 62.5 mg/day. Oxygenation and radiographic appearance improved progressively, with the ratio of arterial oxygen tension to inspired oxygen fraction rising from 72 to 343 by day 5 in the first patient and from 72 to 357 by day 11 in the second, permitting successful liberation from the ventilator. Conclusion: In these two aetiologically distinct patients, early low-dose methylprednisolone added to lung-protective ventilation was associated with rapid clinical and radiographic recovery. The series supports an individualised, aetiology- and phenotype-aware approach to adjunctive corticosteroid therapy in ARDS rather than uniform application or avoidance.